THE USE OF SPEECH ACTS IN KHURSHID DAVRON'S POEM "I PUT MY HEAD ON YOUR CHEST (American Journal of Research in Humanities and Social Sciences, 2026)
This article examines the use of speech acts in the process of verbal communication. It analyzes their linguistic and pragmatic features, as well as their role in revealing the aesthetic nature of a literary text. Special attention is given to the expression of the speaker’s emotions and intentions and to the significance of speech acts in uncovering the content and ideas of a literary work.